Ceria-boosted Ni/Al2O3 catalysts for enhanced H2 production via acetic acid dry reforming - Nguyen, Anh-Tam; Ng, Kim Hoong; Kumar, Ponnusamy Senthil; Pham, Thuy-Phuong T.; Herma Dina, Setiabudi; Yusuf, Mohammad; Pham, Le Kim Hoang; Thao, Bui T. Thu; Aishah, Abdul Jalil; Mahadi, Bahari; Al-Kahtany, Khaled; Vo, Dai-Viet N. (Elsevier Ltd., 2024)
Acetic acid dry reforming (ADR) is a promising route for sustainable H2 generation. However, coke inhibition during ADR is the main challenge and not resolved by using suitable promoted catalysts. In this work, Ce pro motion on 10%Ni/Al2O3 catalysts with 1-5 wt%Ce was evaluated for ADR at varied temperatures of 923–998 K and stoichiometric feed in a fixed-bed rig. CeO2 addition of 1–3% enhanced metal dispersion, and surface area whilst basic CeO2 character significantly boosted the concentration and density of basic sites on catalysts. Particularly, the CO2 uptake of promoted catalysts was about 2.49–3.73 times greater than that of counterpart sample. CH3COOH and CO2 conversions were enhanced with rising Ce loading and the highest reactant con versions were observed at 3 wt%Ce. The improved adsorption of acidic CH3COOH and CO2 molecules due to increasing amount of basic sites as well as redox attributes of CeO2 promoter could be responsible for the enhancement in ADR activity and yield of H2 and CO. The mechanistic two-step pathway for coke suppression induced by CeO2 promotion was elaborated in this work. Generally, carbonaceous species formation on 3% Ce–10%Ni/Al2O3 was considerably reduced about 1.6–2.0 times. H2/CO ratio varied from 0.59 to 0.65 relying on ADR temperature over 3%Ce–10%Ni/Al2O3. These H2/CO values, two times higher than theoretical H2/CO ratio in ADR, are compatible for downstream gas-to-liquid processes to selectively yield high molecular weight olefins. Water formation rate increased from 8.67 ×10 6 to 4.71 ×10 5 molH2O gcat 1 s 1 with rising temperature within 923–998 K on 3%Ce–10%Ni/Al2O3.